Formula Milk Provision with Diarrhea Incident in Infants Aged 0-24 Months - Wirastri, Dwi; Zulfiana, Yesvi (STIKES Yarsi Mataram, 2024)
Background: The World Health Organization (WHO) states that more than2.9 million children under five die from diarrheal disease and it is listed as the main disorder and cause of death in the world after asphyxia, BBLK, infection and puemoша. Based on the diagnosis of health workers, the prevalence of diarrhea in West Nusa Tenggara in children under five is 11% with prevalence in West Nusa Tenggara in fourth place at 13.4%, which indicates that the incidence of diarrhea in children under five in NTB is still above the national average (Ministry of Health of the Republic of Indonesia, 2018) Objective: To determine the relationship between giving formula milk and the incidence of diarrhea in infants age 024 months Method: This type of research uses a quantitative research design with a cross sectional research type. The population in this study is mothers who have babies aged 0-24 months at the Karang Taliwang Community Health Center, Mataram City in January-March 2024, as many as 79 respondents. Sample collection techniques in research This uses non-probability sampling with purposive sampling. Data analysis in this research uses univartat and bivariate analysis. Results: The research results show that there is a relationship between giving formula milk and the incidence of diarrhea. This result is shown by the p value of 0.016 or <0.05. Conclusion: There is a relationship between giving formula milk and the incidence of diarrhea in babies aged 0-24 months.